ORAL DETECT-TRI TO IMPROVE DENTAL AND ORAL DISEASES DETECTION BEHAVIOUR IN HOUSWIVES - Astri Ramdhani; Diyah Fatmasari; Masrifan Djamil (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background Riskesdas 2018 state that the largest proportion of dental problems in Indonesia are damaged/cavities/sick teeth (45.3%). Dental and oral health problems in Gowa Regency, South Sulawesi Province 75.08%, age group 35-44 years 72.86% with DMF-T index higher in women (69.43%) than men (30.57%) ). Community understanding of dental and oral diseases is still low, including housewives with high level of knowledge (9.10%), medium (43.63%), low (47.27%). This can be overcome with a system to detect dental and oral disease so that it is not more severe and early treatment before going to dentist. Objective prove the feasibility test and effectiveness of